2009
DOI: 10.1080/10498850902747837
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preference and Description of Salmon in Four Northern Atlantic Countries and Association with Sensory Characteristics

Abstract: The focus in this article is on the relation between consumer preference and objective description of the product profile of salmon. A consumer study of eight salmon products was carried out in Iceland, Denmark, the Netherlands, and Ireland. In addition, objective sensory profiling using a trained sensory panel was performed on the products, which varied according to storage method, storage time, origin, and species. For five out of eight samples, no significant differences in overall liking between the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
6
2
Order By: Relevance
“…). The importance of juiciness as a positive hedonic driver has been underlined by previous studies and it applies both to meat and fish products . Regarding the connection between firmness and consumer hedonic responses, which were negatively related in this study, the literature evidence is not consistent; some authors support that the higher preference for wild‐caught fish can be attributed to their firmer texture when compared to their farmed counterparts, whereas other studies indicated that the opposite applies, with tender‐textured fish acquiring higher hedonic ratings .…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…). The importance of juiciness as a positive hedonic driver has been underlined by previous studies and it applies both to meat and fish products . Regarding the connection between firmness and consumer hedonic responses, which were negatively related in this study, the literature evidence is not consistent; some authors support that the higher preference for wild‐caught fish can be attributed to their firmer texture when compared to their farmed counterparts, whereas other studies indicated that the opposite applies, with tender‐textured fish acquiring higher hedonic ratings .…”
Section: Resultscontrasting
confidence: 67%
“…45,[47][48][49][50] Regarding the connection between firmness and consumer hedonic responses, which were negatively related in this study, the literature evidence is not consistent; some authors support that the higher preference for wild-caught fish can be attributed to their firmer texture when compared to their farmed counterparts, whereas other studies indicated that the opposite applies, with tender-textured fish acquiring higher hedonic ratings. 39,40,49 Yet it should be noted that, in general, the ideal intensity point for an attribute is hard to define and very much dependent on the product and the preferences of the population examined within a study. 51 With respect to odor/flavor variations, seafood odor/flavor and butter flavor were identified as positive hedonic drivers, whereas earthy odor/flavor had the opposite effect (Fig.…”
Section: Hedonic Responses and Driverscontrasting
confidence: 77%
See 1 more Smart Citation
“…Some existing studies that analyze consumers' preferences in various countries for salmon imported from abroad include Herrmann et al (1993), Rora et al (2004), Green-Petersen et al (2009), and Muhammad and Jones (2011). In these previous studies, consumers' preferences for imported salmon in various places such as Japan, North America, the European Community (EC), France, Iceland, Denmark, the Netherlands, and Ireland were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of the three aforementioned countries that are important as Japan's marketing targets have not been done. Also, in Herrmann et al (1993) and Green-Petersen et al (2009), differences among salmon-producing countries were not taken into consideration, and in Rora et al (2004) and Muhammad and Jones (2011), salmon-producing countries were taken into consideration, but Japan was not included as one of them. Therefore, no useful information was able to be obtained for international marketing of salmon caught in Japan.…”
Section: Discussionmentioning
confidence: 99%